Use of peroxiredoxin for preconditioning of heterotopic heart transplantation in a rat - N. V. Grudinin; V. K. Bogdanov; M. G. Sharapov; N. S. Bunenkov; N. P. Mozheiko; R. G. Goncharov; E. E. Fesenko; V. I. Novoselov (Вестник трансплантологии и искусственных органов, 2020)
Peroxiredoxin 6 (Prdx6) is an antioxidant enzyme in the human body that performs a number of important functions in the cell. Prdx6 restores a wide range of peroxide substrates, thus playing a leading role in maintaining redox homeostasis in mammalian cells. In addition to peroxidase activity, Prdx6 has an activity of phospholipase A2, thus taking part in membrane phospholipid metabolism. Due to its peroxidase and phospholipase activity, Prdx6 participates in intracellular and intercellular signal transmission, thereby facilitating the initiation of regenerative processes in the cell, suppression of apoptosis and activation of cell proliferation. Given the functions performed, Prdx6 can effectively deal with oxidative stress caused by various factors, including ischemia-reperfusion injury. On an animal model of rat heterotopic heart transplantation, we showed the cardioprotective potential of exogenous recombinant Prdx6, introduced before transplantation and subsequent reperfusion injury of the heart. It has been demonstrated that exogenous Prdx6 effectively alleviates the severity of ischemia-reperfusion injury of the heart by 2–3 times, providing normalization of its structural and functional state during heterotopic transplantation. The use of recombinant Prdx6 can be an effective approach in preventing/alleviating ischemia-reperfusion injury of the heart, as well as in maintaining an isolated heart during transplantation.